2010
DOI: 10.7763/ijesd.2010.v1.73
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Climate Change on Aquaculture

Abstract: Climate change is an additional pressure on top of the many (fishing pressure, loss of habitat, pollution, disturbance, introduced species) which fish stocks already experience. The impact of climate change must be evaluated in the context of other anthropogenic pressures, which often have much greater and more immediate effect. Factors that can shape climate are climate changes. These include such processes as variations in solar radiation, deviations in the Earth's orbit, mountain-building and continental dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…The observed occurrence of caged fish type in fishers’ catch could also underscore the assertions of Agbebi and Fagbenro (2006) and Stanford (2002), who reported that fish culture in cages is associated with species purity risks and fundamental environmental flaws, respectively. The ability of the studied fishers to identify CC factors can impact fish cage culture presents another dimension, enhancing the observations of Yazdi and Shakouri (2010), and Freeman (2017) who reported CC variables generally impact aquaculture.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The observed occurrence of caged fish type in fishers’ catch could also underscore the assertions of Agbebi and Fagbenro (2006) and Stanford (2002), who reported that fish culture in cages is associated with species purity risks and fundamental environmental flaws, respectively. The ability of the studied fishers to identify CC factors can impact fish cage culture presents another dimension, enhancing the observations of Yazdi and Shakouri (2010), and Freeman (2017) who reported CC variables generally impact aquaculture.…”
Section: Discussionmentioning
confidence: 72%
“…Stanford (2002) reported sea cage farming is associated with fundamental environmental flaws, while Yazdi and Shakouri (2010) and Freeman (2017) reported that CC variables generally impact aquaculture. Thus, there is a need for concerted efforts to combat and mitigate the detrimental effects of CC (Agbarevo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There have been relatively few studies that have considered the risks faced by inland freshwater aquaculture farms, despite the large and growing importance of the sector, and emerging concerns and hopes about the role it may play in adaptation (De Silva and Soto, 2009;Yazdi and Shakouri, 2010;Pickering et al, 2011;Callaway et al, 2012;Frost et al, 2012). Most studies of aquaculture farmers have been for coastal systems, and are not primarily interested in climate directly; but rather are focused on understanding more broadly, the risks to yields and profits (Le and Cheong, 2010;Ahsan, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…While scientists and resource managers continue to battle with overfishing, pollution, and a decline in fish stocks, the impact of climate change is also attracting major attention. Variability in climate is modifying the productivity of aquatic ecosystems and thus affecting biological processes and food webs ( Yazdi & Shakouri, 2010 ). These impacts will be widely felt by fish farmers, fishers and the coastal poor through unstable livelihoods, fish availability and quality, and compromised health, safety, and homes ( De Silva & Soto, 2009 ; IPCC, 2007 ; and OECD, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many small-scale fish farmers live poorly due to low income level, low productivity, small pond size, low technology, and inadequate knowledge in aquaculture operations coupled with climate change. Climate change impacts like frequent floods, droughts, erosions, extreme temperature could worsen the situation of small-holder fish farming households through total stock loss, increased mortality, reduced fish yield, damage to ponds/tanks, increase operating cost, and affect their livelihoods ( Allison et al ., 2005 ; De Silva & Soto, 2009 ; Yazdi & Shakouri, 2010 ).…”
Section: Introductionmentioning
confidence: 99%